"دور المعارض في تنشيط السياحة بولاية الوادي (دراسة على عينة من المعارض) " - يوسف, شليق; عبد الغني, زيد; عبد النور, صغير; عبد الرزاق, صالحي (جامعة الوادي - University of Eloued, 2023)
"هدفت دراستنا الى اختبار دور المعارض في تنشيط السياحة وتحقيق الرضا المادي والمعنوي للسائح بمنطقة ولاية الوادي وتم الاعتماد على الاستبيان كأداة لجمع البيانات الاولية حيث تم الاعتماد على 124 استمارة, وبعد التحليل الاحصائي. توصلت الدراسة الى أنه يوجد دور إيجابي للمعارض في تنشيط السياحة وتحقيق الرضا المادي والمعنوي للسائح بولاية الوادي. " "Our study aimed to test the role of exhibitions in stimulating tourism and achieving material and moral satisfaction for tourists in the El-Wadi region The questionnaire was relied upon as a tool for collecting primary data, as 124 questionnaires were used, after statistical analysis. The study concluded that there is a positive role for exhibitions in stimulating tourism and achieving material and moral satisfaction for the tourist in El-Wadi state. "
Keywords: التسويق السياحي, المعارض, المستهلك السياحي; Tourism marketing, exhibitions, the tourist consumer